Advanced textile engineering materials - Ul-Islam, Shahid; Butola, B. S. (Wiley / Scrivener Publishing ; Scrivener Publishing LLC, 2018)
"Advanced Textile Engineering Materials is written to educate readers about the use of advanced materials in various textile applications. In the first part, the book addresses recent advances in chemical finishing, and also highlights environmental issues in textile sectors. In the second part, the book provides a compilation of innovative fabrication strategies frequently adopted for the mechanical finishing of textiles. Market description: The book is written for readers from diverse backgrounds such as textile chemistry, textile engineering, and materials sciences"--